Simulation Study of the Influence of Ultrasonic Energy Flow Density on the Properties of Zirconium-based Amorphous Alloys at Room Temperature. Issue 4 (April 2019) - Liu, Fangping; Liu, Xiao; Lou, Yan
Abstract: Zr-based amorphous alloy was firstly pretreated with ultrasonic-assisted vibration microcompression at different amplitudes and frequencies, and then the samples were compressed till fracture. The process were simulated by using the finite element analysis software ABAQUS. The reliability of the finite element model was validated by comparing the simulation and experimental results. The effect of the energy flow density on the deformation behavior of Zr-based amorphous alloy at room temperature was studied at ultrasonic amplitudes of 0, 19, 27, 36, and 43 μm and frequencies of 20, 25, 30, and 35 kHz. Results showed that with the increasing of ultrasonic amplitude and frequency, the elastic modulus decreased, and the equivalent stress distributions were more uniform, and the formability increased. This was due to the temperature rise and increasing of the free volume concentration of the compressed samples caused by the ultrasonic vibration. However, it is found that the formability of amorphous alloy decreased with the increase of ultrasonic energy flow density when the density increased to approximately I = 9.41×10 8 W·m −2 . The phenomenon was because the temperature rise caused by the ultrasonic heating effect exceeded the termination crystallization temperature of amorphous alloy, and fully crystallizing reaction occurred.